Peer Group Education untuk Pencegahan Stroke Pada Kelompok Hipertensi di Desa Susukan Kecamatan Sumbang Kabupaten Banyumas - Setyo, Arif; Sari, Yunita; Ekowati, Wahyu (Universitas Jenderal Soedirman, Jurusan Keperawatan, 2023)
The prevalence of hypertension in Indonesia is increasing every year. Based on the Basic Health Research (Riskesdas) in 2013 the prevalence of hypertension was 25.8%, while in the 2018 Riskesdas it increased to 34.1%. The results of the study stated that the prevalence of uncontrolled hypertension in Indonesia was high, which was more than 91%. Uncontrolled hypertension can cause stroke. The prevalence of stroke in Indonesia increases every year, based on Riskesdas in 2013 the prevalence of stroke was 7%0, while at Riskesdas in 2018 the prevalence of stroke was 10.9%0. The results of the survey of the hypertension group in Susukan Village, Sumbang Subdistrict showed that the majority of hypertension sufferers had low education (91.67%), low knowledge of hypertension (45.83%), uncontrolled blood pressure >140mmHg (83.33%), stroke prevention behavior was low (54.17%). Implementation methods include training on the introduction of hypertension, stroke risk and the benefits of Peer Group Education for stroke prevention, training on prevention of stroke in the hypertension group through a healthy lifestyle (diet, physical activity and stress management), training in early detection of stroke, training in blood pressure monitoring and style monitoring. life of hypertensive patients to prevent stroke. The results showed 90% of participants increased knowledge about hypertension as measured by HKLS, 90% of participants were able to explain a healthy diet in hypertension for stroke prevention, 100% of participants were able to explain physical activity or exercise in hypertension sufferers, 100% of participants were able to explain psychological stress management in hypertension. , 100% of the group were able to demonstrate blood pressure measurement, 100% of the group were able to fill out a healthy lifestyle monitoring sheet for patients with hypertension, 100% of the group were able to demonstrate early detection of stroke. Conclusion: Training increases the knowledge and skills of partners in stroke prevention effectively.